Coupling of nanofiltration and UV, UV/TiO2 and UV/H2O2 processes for the removal of anti-cancer drugs from real secondary wastewater effluent. Issue 5 (October 2019) - Janssens, R.; Cristovao, M.B.; Bronze, M.R.; Crespo, J.G.; Pereira, V.J.; Luis, P.
Graphical abstract: Highlights: Aggregation of TiO2 in real matrix hinders photocatalytic formation of OH radicals. Complete degradation of ETP and PAC in secondary effluent by direct photolysis. Complete degradation of ETP and PAC in nanofiltration retentate by direct photolysis. CP and IF were not degraded using the conditions tested. Abstract: The detection of anti-cancer drugs in surface waters at ng/L indicates that most wastewater treatment processes currently applied are not effective enough to remove these resilient compounds from wastewater. Therefore alternative treatment processes should be tested to avoid discharges in the environment of drugs that have been linked to genotoxic effects. The innovative contribution of this study stands in coupling nanofiltration with advanced oxidation processes to treat real secondary wastewater effluents spiked with 4 widely consumed anti-cancer drugs. Direct photolysis was found to be extremely effective to degrade etoposide and paclitaxel from the secondary effluent as well as from the highly concentrated retentate produced by nanofiltration. The two drugs were not detected after 10 min of exposure that corresponds to higher than 98% removals given the method detection limits by direct injection. This is equivalent to pseudo-first order degradation rate constants higher than 0.46 min −1, which, to the best of the author's knowledge, has not yet been reported for paclitaxel in the literature. However, none of the tested oxidation processes (UV, UV/TiO2 and UV/H2 O2 ) using the reactor setup, exposure times and concentrations of TiO2 and H2 O2 tested, were able to degrade cyclophosphamide or ifosfamide effectively. Compared to literature data, this is probably related to the low amount of photons received by the treated media. Finally important aggregation of catalyst particles was observed in secondary effluent, and photocatalysis had no advantage compared to the other two processes tested.